Observed Mask Wearing and Presence of SARS-CoV-2 in School Wastewater, San Diego County, CA, 2022 - Fielding-Miller, Rebecca; Gaines, Tommi; Hassani, Ashkan; Le, Tina; Omaleki, Vinton; Flores, Marlene; Majnoonian, Araz; Wijaya, F. Carrissa; Knight, Rob; Karthikeyan, Smruthi; Garfein, Richard S. (American journal of public health (1971), 2025)
Objectives. To test the association between directly observed school masking behaviors and the presence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in school wastewater. Methods. We randomly sampled a subset of schools participating in a translational study on the effectiveness of passive wastewater surveillance in nonresidential K‒12 settings in San Diego County. Trained observers conducted biweekly systematic observations of masking behaviors between March 2 and May 27, 2022. Results. The proportion of individuals observed masking was a significant predictor of detecting SARS-CoV-2 in school wastewater (adjusted odds ratio = 0.91; 95% confidence interval = 0.85, 0.99; P = .034). For every 10% increase in the percentage of observed individuals who were fully masked, the odds of detecting SARS-CoV-2 in school wastewater decreased by nearly 10%. Conclusions. Masking does not need to be perfect to be effective. Mask mandates are unlikely to be reimplemented in US schools, but interventions that encourage moderate increases in masking may have an important role to play in improving children’s health and decreasing the spread of COVID-19 and other respiratory diseases. ( Am J Public Health. 2025;115(4):519–527. https://doi.org/10.2105/AJPH.2024.307925 )